(untitled) (American & British Studies Annual, 2008)
The paper discusses two contemporary slave narratives, Octavia Butler’s Kindred (1979) and J. California Cooper’s Family (1991) in order to demonstrate how African American women writers revision American past. More specifically, the paper demonstrates how both Butler and Cooper challenge the constructed ideas about American national identity, the understanding of which has been shaped by notions of family. Foregrounding miscegenation in their own specific ways (Butler via an interracial marriage that may be read as a “trope of integration”; Cooper via a “multicultural project” in which the history of humankind is presented as a narrative of miscegenation), both writers recast the American nation as a family whose members share a common history.